Fibrous histiocytomas: histopathologic review of 95 cases. - Canelas, MM (2010)
Fibrous histiocytoma (FH) is a heterogeneous tumor composed of fibroblasts, histiocytes, and blood vessels. We conducted a retrospective histopathologic analysis of 95 biopsies, performed over the last 3.5 years, of fibrous histiocytomas to analyze the location, delimitation, epithelial changes, induction of folliculo-sebaceous structures, cellularity, vascularity, collagen pattern, and types of composite cells of the FH. In the majority of the biopsies, we confirmed the classical histopathologic features of fibrous histiocytomas. The presence of lymphoid nodules, mast cells, and sparse infiltrate of inflammatory cells was an interesting finding observed in our study.